Doping Induced Band-gap widening in Transition-metal doped ZnO Nanocrystals - Seidu, A.; Egblewogbe, M.; Gebreyesus, G.; Nkrumah-Buandoh, G. (MRS Advances, 2018)
Pure and transition metal (TM)-doped ZnO nanocrystals were synthesized using a wet-chemical process. Synthesis was carried out in distilled water at 85 °C followed by calcining the as-prepared powders at 280 °C and 600 °C. Co, Mn and Fe doping at 4 and 8 mol % was achieved by adding CoCl2.6H2O, MnCl2 .4H2O and FeCl2 .4H2O respectively during the synthesis. Crystal phase characterization was carried out by X-ray powder diffraction (XRD) which confirmed the formation of ZnO in the wurtzite polymorph. The band gap energy of the nanocrystals was measured by both photoluminescence spectroscopy (using the Near Band Edge Emission) and UV-Vis absorption spectroscopy, using a modified version of the Tauc law. Widening of the band gap energy from 3.23 eV to 3.33 eV with increased doping concentration was observed for all the dopants. Ab-initio simulations of doped and undoped ZnO crystals using density functional theory as implemented in the Quantum Espresso package confirmed the increase in the band gap energies with doping concentration.
Keywords: Crystal growth; Dopant; Nanoscale; Simulation; X-ray diffraction (XRD)